Time-Series Forecasting of PM2.5 and PM10 Concentrations Based on the Integration of Surveillance Images - Yong Wu; Xiaochu Wang; Meizhen Wang; Xuejun Liu; Sifeng Zhu (Sensors)
Accurate and timely air quality forecasting is crucial for mitigating pollution-related hazards and protecting public health. Recently, there has been a growing interest in integrating visual data for air quality prediction. However, some limitations remain in existing literature, such as their focus on coarse-grained classification, single-moment estimation, or reliance on indirect and unintuitive information from visual images. Here we present a dual-channel deep learning model, integrating surveillance images and multi-source numerical data for air quality forecasting. Our model, which combines a single-channel hybrid network consisting of VGG16 and LSTM (named VGG16-LSTM) with a single-channel Long Short-Term Memory (LSTM) network, efficiently captures detailed spatiotemporal features from surveillance image sequences and temporal features from atmospheric, meteorological, and temporal data, enabling accurate time-series forecasting of PM2.5 and PM10 concentrations. Experiments conducted on the 2021 Shanghai dataset demonstrate that the proposed model significantly outperforms traditional machine learning methods in terms of accuracy and robustness for time-series forecasting, achieving R2 values of 0.9459 and 0.9045 and RMSE values of 4.79 μg/m3 and 11.51 μg/m3 for PM2.5 and PM10, respectively. Furthermore, validation results on the datasets from two stations in Kaohsiung, Taiwan, with average R2 values of 0.9728 and 0.9365 and average RMSE values of 1.89 μg/m3 and 5.69 μg/m3 for PM2.5 and PM10 using a pretrain–finetune training strategy, confirm the model’s adaptability across diverse geographical contexts. These findings highlight the potential of integrating surveillance images to enhance air quality prediction, offering an effective supplement to ground-level environmental monitoring. Future work will focus on expanding datasets and optimizing network architectures to further improve forecasting accuracy and computational efficiency, enhancing the model’s scalability for broader regional air quality management.